Insect’s Bioconversion of Organic Waste: A Systematic Literature Review and Bibliometric Analysis - Rochimawati, Nur Riana; Yuwono, Arief Sabdo; Jayanegara, Anuraga; Sintawardani, Neni (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Food waste, a type of solid waste is a significant environmental concern, particularly in developing nations. The utilization of insects as bioconversion agents is becoming more significant due to rapid population expansion and the rise in organic waste on a global scale. The research on waste bioconversion utilizing insects is now limited to a few bug species and lacks long-term strategy and sustainability considerations. This study conducted bibliometric analysis and a comprehensive literature evaluation on studies related to waste bioconversion processes utilizing insect bioconversion agents in publications from 2013 to 2023. A bibliometric analysis will offer an overview of research and collaboration trends in this sector, while a systematic literature review (SLR) will provide summaries on selected issues from relevant works. Studies on waste bioconversion using insects have primarily focused on key factors such as the type of organic waste, the rate of waste reduction achieved, the formulation of substrates tailored to insect nutritional needs, and the downstream utilization of insect biomass as feed or for energy production (biogas, biodiesel, and biomass fuel). Most of the existing research centers on the Black Soldier Fly (169 publications), which has demonstrated high efficiency in reducing organic waste. This concentration on BSF highlights a research gap and potential opportunities for investigating other insect species like crickets, mealworms that may offer different advantages in specific waste types or environmental conditions.